A methodological review of qualitative case study methodology in midwifery research. (23rd February 2016) - Atchan, Marjorie; Davis, Deborah; Foureur, Maralyn
Abstract: Aim: To explore the use and application of case study research in midwifery. Background: Case study research provides rich data for the analysis of complex issues and interventions in the healthcare disciplines; however, a gap in the midwifery research literature was identified. Design: A methodological review of midwifery case study research using recognized templates, frameworks and reporting guidelines facilitated comprehensive analysis. Data Sources: An electronic database search using the date range January 2005–December 2014: Maternal and Infant Care, CINAHL Plus, Academic Search Complete, Web of Knowledge, SCOPUS, Medline, Health Collection (Informit), Cochrane Library Health Source: Nursing/Academic Edition, Wiley online and ProQuest Central. Review Methods: Narrative evaluation was undertaken. Clearly worded questions reflected the problem and purpose. The application, strengths and limitations of case study methods were identified through a quality appraisal process. Results: The review identified both case study research's applicability to midwifery and its low uptake, especially in clinical studies. Many papers included the necessary criteria to achieve rigour. The included measures of authenticity and methodology were varied. A high standard of authenticity was observed, suggesting authors considered these elements to be routine inclusions. Technical aspects were lacking in many papers, namely a lack of reflexivity and incomplete transparency of processes. Conclusion: This review raises the profile of case study research in midwifery. Midwives will be encouraged to explore if case study research is suitable for their investigation. The raised profile will demonstrate further applicability; encourage support and wider adoption in the midwifery setting.